The outcome of the Trendelenburg procedure with stripping vs. no stripping in the management of varicose veins - Mohsin, Jibran; Janjua, Muhammad Haris; Fatima, Jumana; siddique, Muhammad Usman; Naseem, Muhammad Yasir; Zahid, Imdad Ahmad (Journal of Fatima Jinnah Medical University, 2020)
Background: Varicose veins is a common problem in Pakistan with multiple treatment options. One of its recommended and commonly performed surgical treatment includes the flush ligation of Saphenofemoral junction (Trendelenburg procedure) with stripping of great saphenous vein and avulsion of varicosities which is a cumbersome process. This study aims to evaluate the effect of stripping of great saphenous vein on the recurrence rate. Patients and methods: A randomized controlled trial was conducted in the Surgical Unit I, Services Hospital, Lahore over a period of 22 months from 20-09-2016 to 20-07-2018. Seventy patients were divided equally into two groups of 35 patients each i.e. Trendelenbrug procedure and avulsion of varicosities with stripping down to the knee, (Group A) versus Trendelenbrug procedure and avulsion of varicosities without stripping (Group B). Recurrence at 12 weeks was noted. SPSS version 17.0 was used to analyze data. Comparison of recurrence and stratified confounding factors such as age, gender, and BMI were assessed by the chi-square test (significant p-valve ≤0.05). Results: In group A, 32 out of 35 patients were male (91.43%) and 3 (8.57%) were female. While in group B, 31 out of 35 patients were male (88.87%) and 4 (11.43%) were female. Four out of 35 (11.43%) patients in group A whereas 6 (17.14%) group B patients (p-value=0.494) had a recurrence in the perforators below the knee at 12 weeks. Stratification (p-values) of recurrence rate with respect to age (<40 years: 0.41 versus ≥ 40 years:0.905), gender (female: p-value not applicable versus male: 0.96) and BMI was done (<25 kg/m2: 0.36 versus ≥ 25 kg/m2: 0.901) Conclusions: Stripping does not significantly affect the outcome of varicose vein surgery in relation to the recurrence rate at 12 weeks and recurrence was independent of age, gender, and BMI of patients.